(3GdUGQe GdbQVGH aj fMQ SqH CcGQe GdCUMGHs - (3YKeGf Hf SfO GdfLOj GdHUQj, HOQ GdOjf, GHf SfO , J (B1242 (3g` s
(3ChdgG (B:s
(3Efj hbaJ Ydi OjhGf WqQRJ MhGTjg HGdHgJGf, hGeJdCJ RhjGg Hcd RhQ hHjfJ eG ajg ef bHM YhQ s
(3BNQgG (B:s
(3aCgd GdUdGI GdYHgQjI eWQakG Edi NjQ bWH ddfHjjf NGJekG JOhe eY GdJSdje Ke Ydjce cBd CVGAhG aj SeGA GdecGQe Je GdOjhGf s
(3ChQGbgG GdChdi eVWQHI GdJQJjH hHgG fXGe GdJYbjHIs
(3hCcedJ GdhQbI GdCNjQI HNW eZGjQ YGe (B1303(3g`s
(3OjhGf TYQ QO Ydi OYHd GdNRGYj aj bUGFOg GdJj SqH ajgG GdUMGHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs